IMPROVING THE QUALITY OF PAUD TEACHERS THROUGH HUMAN RESOURCE MANAGEMENT IN PSP 2 - Erva Elli Kristanti; Yoyok Febrijanto (Suluh Adiluhung Publisher (SAPub), 2024)
The aim of community service was to improve the quality of teachers implemented by PAUD institutions in Kediri City that participate in PSP 2 by involving all school members and carried out in the form of coaching, counseling, mentoring, motivation, and empowerment as human resource management. The implementation of community service showed that PAUD institutions also implement and carry out several programs to improve the quality of teachers such as comparative studies, training workshops, internal training, study groups, coaching, field visits, workshops, competitions and improving formal education (college). Human resource management is very important in improving the quality of teachers in PAUD institutions. So that PAUD institutions must really pay attention to and maintain human resources in accordance with the provisions of applicable laws.